The mediating role of employees' organisational commitment on the relationship between internal market orientation and employees' retention : Evidence from Malaysian hotel industry - Hamiza, Jamaludin (2014)
Empirical evidence and statistical data show that the hotel industry in Malaysia faces high employee turnover. The hotel industry is not so fortunate in retaining its employees. Though they can be easily hired retention becomes the most challenging job faced by the hotel managers when high turnover gradually increases. There is a research gap in this area since most of the previous researchers focused their studies on employee turnover. This study focuses on employee retention strategy. On this note, the research framework was developed based on the Herzberg Two-Factor Theory and the Social Exchange Theory. The current study aims to identify whether factors, such as internal market orientation and employees’ organisational commitment have significant influence on employee retention in the Malaysian hotel industry. Out of the 600 personally administered questionnaires to the frontline hotel employees, 392 sets of questionnaires were returned and found useable, constituting about 65 per cent rate of return. The data was analysed using the SPSS package version 20. The findings indicated that all the three components of internal market orientation, namely internal market intelligence generation, internal market intelligence dissemination and responsiveness to market intelligence, have a significant and positive relationship with employees’ organizational commitment and employee retention. Employees’ organizational commitment was also found to have a positive and significant relationship with employees’ retention. The study also revealed that only affective and normative commitments serve as mediators in the relationship between internal market orientation and employees’ retention but failed to support continuance commitment as the mediator. In addition, this study also established internal market orientation as the hygiene factor and not as the motivation factor. This study concludes with a discussion on the theoretical and practical contributions, study limitations and suggestions for future research.